“La Gestión Administrativa y su incidencia en el desarrollo del talento humano de la cooperativa de ahorro y crédito sagrada familia LTDA., sucursal Riobamba periodo 2015“ - Lemache Pérez, Andrea Yadira (2016)
This research work arises from the need to improve administrative management in terms of human talent credit union Sagrada Familia Ltda., In the city of Riobamba, because there are shortcomings in the allocation of responsibilities as not taken into account the appropriate professional profile to hold such office or position and thus confusion of roles which would imply a conflict between employees by not identifying their functions, in the same way uncomfortable because they do not exercise their work according to their profiles. Because of these reasons arises this research entitled: "THE ADMINISTRATIVE AND ITS IMPACT ON THE DEVELOPMENT OF HUMAN TALENT credit union SAGRADA FAMILIA LTDA. , BRANCH RIOBAMBA PERIOD 2015 ", whose main objective is to determine the incidence of Administrative Management in Human Resource Development, through a study involving managerial, administrative and operational staff focused on designing a manual functions for talent human that allows the strengthening and development of all employees of the Cooperative. This research work is structured by the following chapters: First Chapter: It describes the problem entirely as is currently the financial institution further the objectives and rationale for detailed research. Chapter Two: It consists of the theoretical and conceptual framework which allowed strengthening and have extensive knowledge regarding the problem under study. Third Chapter: It consists of the methodological framework, type of research, research design, techniques and research tools, sample and data processing. Fourth Chapter, It points out the conclusions and recommendations of the investigation. Fifth Chapter. It consists of the proposal it contains the model manual functions for human talent which will help to properly establish the roles and responsibilities of employees of the credit union Sagrada Familia Ltda, in line with their professional profiles and thus better develop their skills and abilities.